2010
DOI: 10.1002/cncr.24799
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeted radioimmunoscintigraphy in patients with primary colorectal cancer using a bispecific anticarcinoembryonic antigen CEA X anti‐di‐diethylenetriaminepentaacetic acid F(ab′)2 antibody

Abstract: BACKGROUND: Antibody-based imaging agents are available commercially, but their success has been limited, mainly because of low contrast and the emergence of 2-fluoro-2-deoxy-D-glucose-positron emission tomography (FDG-PET) scanning. In pretargeting, administration of the radionuclide is separated from the antibody, thereby enhancing image contrast and allowing detection at earlier time points after injection. METHODS: The authors conducted an open-label, single-arm trial that assessed a pretargeting procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Additional studies using streptavidin-biotin pretargeting are underway for patients with AML, acute lymphoblastic leukemia (ALL), and myelodysplastic syndrome (MDS) (Pagel & Press et al ., unpublished data). Pretargeting using antibodies to carcinoembryonic antigen (CEA) 116 was tested in colorectal cancer (CRC) 117 , small-cell lung cancer (SCLC) 118 , and medullary thyroid carcinoma 116, 119 ; NR-LU-10 in CRC 115 ; CC49 in gastrointestinal cancer 114 ; and CD20 monoclonal antibodies in NHL 113, 115 —all with variable success. A three-step approach using biotinylated monoclonal antibodies, followed by avidin-streptavidin and then biotinylated radiometal-chelate, was also applied to patients with glioma with encouraging results 120, 121 .…”
Section: Pilot Prit Human Studiesmentioning
confidence: 99%
“…Additional studies using streptavidin-biotin pretargeting are underway for patients with AML, acute lymphoblastic leukemia (ALL), and myelodysplastic syndrome (MDS) (Pagel & Press et al ., unpublished data). Pretargeting using antibodies to carcinoembryonic antigen (CEA) 116 was tested in colorectal cancer (CRC) 117 , small-cell lung cancer (SCLC) 118 , and medullary thyroid carcinoma 116, 119 ; NR-LU-10 in CRC 115 ; CC49 in gastrointestinal cancer 114 ; and CD20 monoclonal antibodies in NHL 113, 115 —all with variable success. A three-step approach using biotinylated monoclonal antibodies, followed by avidin-streptavidin and then biotinylated radiometal-chelate, was also applied to patients with glioma with encouraging results 120, 121 .…”
Section: Pilot Prit Human Studiesmentioning
confidence: 99%
“…Former studies showed pretargeted immuno-PET and -SPECT with radionuclides, such as 68 Ga, 18 F, 124 I, and 99m Tc (7,(12)(13)(14), but these methods cannot be used for dosimetric calculations for therapy. The half-life of 68 Ga (68 min) is not matched with the therapeutic radionuclide.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic efficacy of PRIT with TF2 and 177 Lu-IMP288 was demonstrated previously in mice with subcutaneous LS174T xenografts (5). Furthermore, several clinical studies with bsmAb and 111 Inlabeled haptens for pretargeted immuno-SPECT showed high sensitivity (18)(19)(20)(21). In patients, immuno-SPECT can be used to guide individual treatment, because this imaging modality can be repeated at multiple time points.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the tumor uptake was ~10% ID/g for 68 Ga-IMP-288 and the tumor-to-blood ratio was ~70 [112]. Moreover, in a preliminary clinical trial, an anti-CEA/anti-DTPA bispecific antibody paired with an 111 In-di-DTPA peptide was employed in patients with primary colorectal cancer [113]. Among the intervals studied, the best imaging contrast was obtained with a 4 day interval, with resulting tumor-to-background ratios of 5.1 to 14.2 at 24 hours after injection of the radiolabeled peptide.…”
Section: Alternative Strategies Of Pet Radioimmunoimagingmentioning
confidence: 99%